Deciphering mechanisms of staphylococcal biofilm evasion of host immunity - Hanke, Mark L.; Kielian, Tammy (Frontiers in Cellular and Infection Microbiology, 2012)
Biofilms are adherent communities of bacteria contained within a complex matrix. Although host immune responses to planktonic staphylococcal species have been relatively well-characterized, less is known regarding immunity to staphylococcal biofilms and how they modulate anti-bacterial effector mechanisms when organized in this protective milieu. Previously, staphylococcal biofilms were thought to escape immune recognition on the basis of their chronic and indolent nature. Instead, we have proposed that staphylococcal biofilms skew the host immune response away from a proinflammatory bactericidal phenotype towards an anti-inflammatory, pro-fibrotic response that favors bacterial persistence. This possibility is supported by recent studies from our laboratory using a mouse model of catheter-associated biofilm infection, where S. aureus biofilms led to the accumulation of alternatively activated M2 macrophages that exhibit anti-inflammatory and pro-fibrotic properties. In addition, relatively few neutrophils were recruited into S. aureus biofilms, representing another mechanism that deviates from planktonic infections. However, it is important to recognize the diversity of biofilm infections, in that studies by others have demonstrated the induction of distinct immune responses during staphylococcal biofilm growth in other models, suggesting influences from the local tissue microenvironment. This review will discuss the immune defenses that staphylococcal biofilms evade as well as conceptual issues that remain to be resolved. An improved understanding of why the host immune response is unable to clear biofilm infections could lead to targeted therapies to reverse these defects and expedite biofilm clearance.